Organization and Standardization of Sustainability Reporting - N. I. Dorosh; I. V. Horobets (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The objective of the studyis to highlightthe content, purposes, standards and applications of sustainability reporting, to present a comparative analysisof the sustainability reporting framework from the point of view of internal and external users, to analyze government regulations and best practices of development and presentation of sustainability reporting.Main components of sustainability, definitions of sustainability, content of sustainability reporting, the International Reporting Framework, the reporting content under Global Reporting Initiative (GRI), numbers of companies preparing report by GRI are illustrated. One of the most important tasks of this article is to clarify the position of the Ukrainian business entities with respect to sustainability reporting and outline the ways to improve it by use of world’s best practices.A review of sustainability reporting practices at Ukrainian companies is made. It shows that Ukrainian enterprises developing and presenting sustainability reporting based on GRI framework can be divided into groups: large multinational companies with divisions in Ukraine (Coca-Cola, Deloitte, EY, KPMG, British American Tobacco, Nestle, etc.); Ukrainian nature companies (Arcelor, VEON, Energoatom (first state company in Ukraine adopted GRI) companies of SKM group: DTEK, Ukrtelecom, UMG, etc.). The numbers of Ukrainian companies who develop, present and disclose information on sustainability remain to be low due to economic, geo-politic, socio-cultural factors. Recommendations on further development of sustainability reporting in Ukraine are given.